2010
DOI: 10.1007/s10439-010-0110-7
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of High-Frequency Oscillatory Air Flow and Convective Mixing in a CT-Based Human Airway Model

Abstract: High frequency oscillatory ventilation (HFOV) is considered an efficient and safe respiratory technique to ventilate neonates and patients with acute respiratory distress syndrome. HFOV has very different characteristics from normal breathing physiology, with a much smaller tidal volume and a higher breathing frequency. In this work, the high frequency oscillatory flow is studied using a computational fluid dynamics (CFD) analysis in three different geometrical models with increasing complexity: a straight tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 44 publications
4
63
0
3
Order By: Relevance
“…This allows turbulent structures to establish before the flow reaches that lower region of trachea. The current LES settings and treatment are consistent with other existing studies of pulmonary CFD Banerjee, 2015a, 2015b;Alzahrany et al, 2014a;Choi et al, 2010;Gemci et al, 2008;Jayaraju et al, 2008;Nagels and Carter, 2009). …”
Section: Breathing and Boundary Conditionssupporting
confidence: 85%
“…This allows turbulent structures to establish before the flow reaches that lower region of trachea. The current LES settings and treatment are consistent with other existing studies of pulmonary CFD Banerjee, 2015a, 2015b;Alzahrany et al, 2014a;Choi et al, 2010;Gemci et al, 2008;Jayaraju et al, 2008;Nagels and Carter, 2009). …”
Section: Breathing and Boundary Conditionssupporting
confidence: 85%
“…The peak Re of HFOV is about three times higher than that of NORM and HFNR; thus, the flow in HFOV is expected to be most turbulent even at phase change. Choi et al (17) noted that convective mixing is most effective at peak inspiration because of the aforementioned mode 4 "longitudinal augmented dispersion" at high Re. At end inspiration and expiration, Figure 9 shows the velocity fields in the bifurcation plane at the airway bifurcation between generations 2 and 3.…”
Section: High-frequency Oscillatory Ventilationmentioning
confidence: 98%
“…To map the flow regimes of all airway segments in the lung, Choi et al (17) used a multidetector row computed tomography (MDCT)-based 3D airway model (up to seven generations) coupled to a 1D 25-generation conducting airway tree of the same subject (see the insert in Fig. 1) generated by a volume filling technique (88,89) to examine three breathing conditions.…”
Section: Flow Regimesmentioning
confidence: 99%
“…A range of 0.5oy þ o3 was also reported by Dehbi (2011). For realistic complex geometries like the present CT-scan based lung model geometry, a tetrahedral mesh style has been considered appropriate in many past studies (Alzahrany and Banerjee, 2015;Choi et al, 2010;Farkas and Balashazy, 2007;Gemci et al, 2008;Luo et al, 2014). The mesh sensitivity was examined and it was found that a mesh of size 2.42 Â 10 6 elements resolves 491% of turbulence kinetic energy for all considered HFOV frequency and is considered appropriate as it resolves 480% of the total energy (Pope, 2001).…”
Section: Numerical Methods and Experimental Validationmentioning
confidence: 60%